Physicochemical properties of dragon fruit peel pectin and commercial pectin: a comparison - Muhammad, Nurul Widad Fitri; Ahmad Fadzillah, Nurrulhidayah; Mohd. Salleh, Hamzah; Othman, Rashidi; Rohman, Abdul (Rynnye Lyan Resources, 2019)
Dragon fruit is a tropical fruit belongs to Cactae family of genus Hylocereus. Popularly known as ‘buah Naga’ in Malay, Dragon fruit is not only preferred for its unique taste, but this fruit is also nutritionally and medicinally attractive for consumers. The Dragon fruit flesh is usually eaten raw or it is blended into juice while the remaining peel is discarded. In order to minimize this waste from Dragon fruit consumption, an idea of transforming the peel of Dragon fruit into edible pectin has been proposed. Pectin can be found in food products as gelling agent and it is used to maintain the quality of foods. Market demand for pectin is increasing annually and in order to meet the supply-demand, researchers are working towards obtaining pectin from available non-conventional sources. In this study, pectin was extracted from Dragon fruit peel by hot acid extraction. Optimum conditions (pH 3.5, 75 minutes of extraction) were considered to yield the highest amount of pectin. Distilled water was used as solvent and the acidic environment was achieved with dilute HCl. The extracted pectin was categorized as high methoxyl pectin based on estimated degree of esterification (52%). FTIR analysis detected pectin’s functional groups characteristics of carbohydrates, and the extracted pectin identity was confirmed by comparison with commercial pectin. Melting temperature (Tm) and melting enthalpy (ΔHm) of the Dragon fruit peel pectin analysed by DSC were 122.01 oC and 385.40 mJ, respectively. The values were found to be higher than those of commercial pectin (107.11 oC and 77.81 mJ, respectively). Ash content, water and oil holding capacity (WHC, OHC) and swelling capacity (SC) are among other characteristics of extracted pectin that were analysed. Analysis of variance (ANOVA) of these characteristics showed there were no significant difference (p> 0.05) when compared with commercial pectin. However, there was a significant difference (p< 0.05) in moisture content between the Dragon fruit peel pectin samples and commercial pectin. Pectin gel was formulated from extracted pectin and tested for its cohesiveness, gumminess and hardness. Result obtained indicates the texture of this pectin gel has no significant difference compared with pectin gel made from commercial pectin. Therefore, we concluded that the Dragon fruit peel has a great potential to be an alternative pectin substitute.